A discovery-based proteomics approach identifies protein disulphide isomerase (PDIA1) as a biomarker of β cell stress in type 1 diabetesResearch in context - Farooq Syed; Divya Singhal; Koen Raedschelders; Preethi Krishnan; Robert N. Bone; Madeline R. McLaughlin; Jennifer E. Van Eyk; Raghavendra G. Mirmira; Mei-Ling Yang; Mark J. Mamula; Huanmei Wu; Xiaowen Liu; et al. (EBioMedicine, 2023)
Summary: Background: Stress responses within the β cell have been linked with both increased β cell death and accelerated immune activation in type 1 diabetes (T1D). At present, information on the timing and scope of these responses as well as disease-related changes in islet β cell protein expression during T1D development is lacking. Methods: Data independent acquisition-mass spectrometry was performed on islets collected longitudinally from NOD mice and NOD-SCID mice rendered diabetic through T cell adoptive transfer. Findings: In islets collected from female NOD mice at 10, 12, and 14 weeks of age, we found a time-restricted upregulation of proteins involved in stress mitigation and maintenance of β cell function, followed by loss of expression of protective proteins that heralded diabetes onset. EIF2 signalling and the unfolded protein response, mTOR signalling, mitochondrial function, and oxidative phosphorylation were commonly modulated pathways in both NOD mice and NOD-SCID mice rendered acutely diabetic by T cell adoptive transfer. Protein disulphide isomerase A1 (PDIA1) was upregulated in NOD islets and pancreatic sections from human organ donors with autoantibody positivity or T1D. Moreover, PDIA1 plasma levels were increased in pre-diabetic NOD mice and in the serum of children with recent-onset T1D compared to non-diabetic controls. Interpretation: We identified a core set of modulated pathways across distinct mouse models of T1D and identified PDIA1 as a potential human biomarker of β cell stress in T1D. Funding: NIH (R01DK093954, DK127308, U01DK127786, UC4DK104166, R01DK060581, R01GM118470, and 5T32DK101001-09). VA Merit Award I01BX001733. JDRF (2-SRA-2019-834-S-B, 2-SRA-2018-493-A-B, 3-PDF-20016-199-A-N, 5-CDA-2022-1176-A-N, and 3-PDF-2017-385-A-N).